1995
DOI: 10.1007/s001250050293
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of urinary albumin excretion rate to ambulatory blood pressure and erythrocyte sodium-lithium countertransport in NIDDM

Abstract: SummaryIncreased erythrocyte sodium-lithium countertransport rate is found in non-diabetic subjects with essential hypertension, and in insulin-dependent diabetic subjects with nephropathy. However, relationships between these variables in non-insulin-dependent diabetic subjects are ill-defined. In order to characterise the relationships between blood pressure, urinary albumin excretion, and erythrocyte sodium-lithium countertransport, 66subjects with non-insulin-dependent diabetes were studied. Urinary albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In type 1 diabetes, some [ 35, 36], but not all [ 37], investigators found increased Na + /Li + counter‐transport in patients with nephropathy, compared with matched patients without nephropathy. Two [ 38, 39] of four studies in type 2 diabetic patients with nephropathy also reported increased Na + /Li + exchange. Considerable overlap existed between the groups, possibly because non‐genetic factors influence Na + /Li + exchange activity, including hyperlipidaemia, hypokalaemia, etc.…”
Section: Factors Predisposing To Diabetic Nephropathy In Type 2 Diabetesmentioning
confidence: 99%
“…In type 1 diabetes, some [ 35, 36], but not all [ 37], investigators found increased Na + /Li + counter‐transport in patients with nephropathy, compared with matched patients without nephropathy. Two [ 38, 39] of four studies in type 2 diabetic patients with nephropathy also reported increased Na + /Li + exchange. Considerable overlap existed between the groups, possibly because non‐genetic factors influence Na + /Li + exchange activity, including hyperlipidaemia, hypokalaemia, etc.…”
Section: Factors Predisposing To Diabetic Nephropathy In Type 2 Diabetesmentioning
confidence: 99%
“…Furthermore, increased Na + \Li + CT activity has been shown to be associated with left ventricular hypertrophy [18,19,[24][25][26], coronary heart disease (CHD) [27], hyperlipidaemia [4,7,8] and urinary albumin excretion [1,18,28]. A relationship between Na + \Li + CT activity and diabetic nephropathy is less evident [4,29,30].…”
Section: Introductionmentioning
confidence: 99%